Site Prediction Model for the over Rooftop Path in a Suburban Environment at Millimeter Wave - Young Keun Yoon; Kyung Won Kim; Young Jun Chong (International Journal of Antennas and Propagation)
This paper proposes the site-specific pathloss model for a small town in a suburban environment at millimeter wave. Also, the site general characteristics are provided in the entire measurement area of the small town. The proposed pathloss model is based on the moving measurement campaign according to the distance between a transmitter and a receiver in the candidate millimeter wave band or future five-generation service. In addition, the probability characteristics of pathloss such as the cumulative density function are shown to estimate the spreading characteristics of the wideband signal with a five-hundred-MHz bandwidth. Measurement was performed for the small town in a suburban covered with low-rise commercial restaurants or houses. Transmitting signals propagate through the over rooftop of low-rise houses of average ten meters height. Their multipath signals may be arrived at a receiving station located at the below roof of the house by reflection, diffraction, and scattered mechanism. A current propagation model for the over rooftop is based on generic or geometrical optic equations in a fully non-line-of-sight environment. But, non-line-of-sight cases in a realistic suburban environment include partly the open space between houses. Therefore, the definition of the propagation model of this sight-specific case is very important so clearly as to show the difference for the over rooftop according to the different displacements of houses in a non-line-of-sight environment. Finally, we suggest the improved propagation model of pathloss that can reflect various environments in a small town.